2009
DOI: 10.1523/jneurosci.1779-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Hypoxia-Inducible Factor (HIF) Prolyl-Hydroxylase 1 Mediates Neuroprotection against Normoxic Oxidative Death via HIF- and CREB-Independent Pathways

Abstract: Oxidative stress contributes to tissue injury in conditions ranging from cardiovascular disease to stroke, spinal cord injury, neurodegeneration, and perhaps even aging. Yet the efficacy of antioxidants in human disease has been mixed at best. We need a better understanding of the mechanisms by which established antioxidants combat oxidative stress. Iron chelators are well established inhibitors of oxidative death in both neural and non-neural tissues, but their precise mechanism of action remains elusive. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 62 publications
(68 reference statements)
4
87
1
Order By: Relevance
“…Instead, siRNA directed against prolyl 4-hydroxylase isoform 1 diminished neuronal death induced by oxidative stress through HIF-independent mechanisms (Siddiq et al, 2009). In addition, structurally diverse PHIs (including DFO) protect neurons in an in vitro model of Huntington's disease through a mechanism independent of HIF-1 function (Niatsetskaya et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, siRNA directed against prolyl 4-hydroxylase isoform 1 diminished neuronal death induced by oxidative stress through HIF-independent mechanisms (Siddiq et al, 2009). In addition, structurally diverse PHIs (including DFO) protect neurons in an in vitro model of Huntington's disease through a mechanism independent of HIF-1 function (Niatsetskaya et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory used a cell permeant peptide inhibitor of all three HIF PHD isoforms but not the collagen PHDs to prevent oxidative death of cortical neurons (Siddiq et al, 2005). RNA interference showed that deletion of HIF PHD1 but not deletion of HIF PHD2 or HIF PHD3 can provide protection against oxidative death of neurons (Siddiq et al, 2009). Conditional deletion of all HIF PHDs has been shown to affect cell viability in response to developmental stimuli in sympathetic neurons (HIF PHD3; Bishop et al, 2008), ischemia in muscle (HIF PHD1; Aragones et al, 2008), and ischemia in the heart (HIF PHD2; Holscher et al, 2011), but these studies while promising, seem to have limited import for posttreatment protection.…”
Section: Hypoxia-inducible Factor Prolyl Hydroxylase Inhibition As Anmentioning
confidence: 99%
“…Increases in HIF-1a transcription could overwhelm the ability of neurons to degrade HIF-1a and lead to its stabilization. In this scheme, HIF-1a induction may be a biomarker of other genes that are known to abrogate oxidative stress, such as MnSOD (9), rather than being responsible for protection itself (49). Of course, it is also possible that benzimidazoles act post-transcriptionally rather than transcriptionally to enhance the interaction of HIF-1a (and other proteins) with Septins, a group of microtubule polymerizing guanine nucleotide-binding proteins which lead to HIF-1a stabilization in tumors (2).…”
Section: Discussionmentioning
confidence: 99%